SAT0512 Safety and efficacy of lenabasum in refractory skin-predominant dermatomyositis subjects treated in an open label extension of trial jbt101-dm-001. (12th June 2018) - Werth, V.P.; Patel, B.; Concha, J.S.; Okawa, J.; Pearson, D.; Hejazi, E.; Feng, R.; Cornwall, C.; Dgetluck, N.; Constantine, S.; Aggarwal, A.; White, B.
Abstract : Background: Lenabasum (aka anabasum, JBT-101) is a selective cannabinoid receptor type 2 agonist that activates resolution of innate immune responses. It is a synthetic, oral, non-immunosuppressive small molecule. Lenabasum showed acceptable safety and tolerability and evidence of clinical benefit in 22 subjects with refractory, skin-predominant dermatomyositis (DM) in Phase 2 trial JBT101-DM-001 (NCT02466243 ). Objectives: This study evaluated safety and efficacy of open-label dosing of lenabasum in moderately-to-severely active skin-predominant DM in subjects who were refractory to or intolerant of hydroxychloroquine treatment. Methods: Subjects who completed the double-blind placebo-controlled (DBPC) part of JBT101-DM-001 with 12 weeks of active dosing and 4 weeks of safety follow-up were eligible to receive lenabasum 20 mg BID in an open-label extension (OLE). Safety and efficacy evaluations were done at Week 4 after the start of OLE, then every 8 weeks thereafter. Results: 20/22 (91%) eligible subjects enrolled in the OLE and 17/20 (85%) were on baseline immunosuppressive drugs. There was a mean interval of 31 weeks (range 4–92 weeks) from the end of active DBPC dosing and the start of the OLE, during which time subjects remained on background medications prior to adding lenabasum in the OLE. At the time of OLE data cut-off, no subjects had discontinued, all 20 subjects in the OLE completed visits through Week 12 and 11 subjects completed visits through Week 28. During the 28 weeks of OLE dosing, adverse events (AEs, n=30) occurred in 14/20 (70%) subjects. Only 1 subject had a moderate AE, all other AEs were mild. Four (20%) subjects had AEs considered related to lenabasum. The only AE that occurred in more than 1 subject was DM flare (n=2, 10%). During the OLE, there was improvement from the beginning of the OLE dosing and from the study start in Cutaneous Dermatomyositis Activity and Severity Index (CDASI) Activity score and physician Likert assessments of global disease activity, skin disease activity and extramuscular disease activity. Similarly, there were improvements in multiple patient-reported outcomes, including patient 10 cm VAS scores of global disease activity, skin disease activity, itch and pain, as well as the Skin-dex-29 symptoms domain and PROMIS-29 physical function, fatigue, pain interference, and anxiety domains. Selected efficacy outcomes are shown in figure 1 as change from study start during two periods: 1) "off treatment" from the end of active DBPC dosing to the start of OLE, dotted line; and 2) OLE dosing, solid line. Conclusions: Lenabasum continues to have a favourable safety and tolerability profile in the OLE of the Phase 2 trial JBT101-DM-001 with no severe or serious AEs or study discontinuations related to lenabasum. The CDASI activity score and multiple other physician and patient-reported outcomes improved from study start and start of the OLE, although open-label nature of dosing with lenabasum is acknowledged. These data support further testing of lenabasum for the treatment of DM. Disclosure of Interest: V. Werth Consultant for: Corbus Pharmaceuticals, Inc., B. Patel: None declared, J. Concha: None declared, J. Okawa: None declared, D. Pearson: None declared, E. Hejazi: None declared, R. Feng: None declared, C. Cornwall Employee of: Corbus Pharmaceuticals, Inc., N. Dgetluck Employee of: Corbus Pharmaceuticals, Inc., S. Constantine Employee of: Corbus Pharmaceuticals, Inc., A. Aggarwal Employee of: Corbus Pharmaceuticals, Inc., B. White Employee of: Corbus Pharmaceuticals, Inc.